INTEGRATING AYURVEDA FOR COST-EFFECTIVE TYPE 2 DIABETES CONTROL : A CASE STUDY - Karanjgaonkar, Pradnya Prashant (International Journal of Research -GRANTHAALAYAH, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic, lifestyle-related metabolic disorder imposing significant health and financial burdens globally. This case study evaluates a Lifestyle Intervention Holistic (LIH) model incorporating Ayurvedic principles in a T2DM patient. Over 12 months, the intervention led to marked improvements in glycaemic control, reduced medication reliance, and enhanced quality of life, alongside a 96% reduction in medication costs. These results support the potential of Ayurveda-based LIH models as sustainable and cost-effective alternatives for diabetes management